60-GHz Millimeter-Wave Channel Measurements and Modeling for Indoor Office Environments - Wu, Xianyue; Wang, Cheng-Xiang; Sun, Jian; Huang, Jie; Feng, Rui; Yang, Yang; Ge, Xiaohu (IEEE transactions on antennas and propagation, 2017)
The millimeter-wave (mmWave) band will be used for the fifth-generation communication systems. In this paper, 60-GHz mmWave channel measurements and modeling are carried out for indoor office environments. The rotated directional antenna-based method and uniform virtual array-based method are adopted and compared to investigate the 60-GHz channel in a 3-D space, simultaneously covering azimuth and coelevation domains. The multipath component parameters including power, delay, azimuth, and elevation angles are estimated with the space-alternating generalized expectation-maximization estimation algorithm, and then processed with the K-means clustering algorithm. An extended Saleh-Valenzuela model with both delay and angular cluster features is used to characterize the measured channel, and the intercluster and intracluster parameters are extracted. We find that the azimuth departure angles are diverse and highly related to the antenna position and measurement environment, while the elevation departure angles are more related to the antenna height difference and confined in a relatively small direction range. The azimuth angle spread is much larger than the elevation angle spread either in global level or in cluster level. The results agree with the studies in the literature and channel models in IEEE standards.